2018
DOI: 10.1002/jtr.2241
|View full text |Cite
|
Sign up to set email alerts
|

The moderating role of nationality in residents' perceptions of the impacts of tourism development in the United Arab Emirates

Abstract: The purpose of this paper is to investigate residents' perceptions of tourism impacts and whether nationality moderates the relationship between these perceptions and support for tourism development in the UAE. Using data collected from 979 respondents from the UAE, a questionnaire assessed the moderating effect of nationality on residents' perceptions of the social, cultural, environmental, and economic impacts of tourism. Social exchange theory is used as a theoretical framework for this study because it con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 82 publications
(133 reference statements)
3
11
2
Order By: Relevance
“…One possible reason is that expats are attracted to live in the UAE mainly in search of better economic opportunities; therefore, they would be more concerned about the economic impact while the nationals are more anxious about their country's social, cultural and environmental impacts. Nevertheless, the results of this study contradict Papastathopoulos et al, (2020); Hammad et al, (2017) and Hammad et al (2019) studies in the way it found that both local and expats perceive the positive socio-cultural aspects of tourism development while both do not perceive any negative socio-cultural aspects of tourism. Remarkably, both residents' groups (citizens and expats) showed positive overall evaluation of tourism impacts and both supported future tourism development by UAE government.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…One possible reason is that expats are attracted to live in the UAE mainly in search of better economic opportunities; therefore, they would be more concerned about the economic impact while the nationals are more anxious about their country's social, cultural and environmental impacts. Nevertheless, the results of this study contradict Papastathopoulos et al, (2020); Hammad et al, (2017) and Hammad et al (2019) studies in the way it found that both local and expats perceive the positive socio-cultural aspects of tourism development while both do not perceive any negative socio-cultural aspects of tourism. Remarkably, both residents' groups (citizens and expats) showed positive overall evaluation of tourism impacts and both supported future tourism development by UAE government.…”
Section: Discussioncontrasting
confidence: 99%
“…Another significant finding of the study is that although the national residents perceived the negative economic and environmental impacts of tourism development, this has no effect on their overall evaluation of tourism impacts or on their support for tourism development. This finding is really noteworthy and contradicts with Hammad et al (2019) study in which results suggest a negative relationship between residents' negative perceptions of social, environmental, and economic impacts of tourism and their support for tourism development in the UAE. The possible explanation for this contradiction between the two studies may be the collapse of tourism revenues because of the COVID-19 pandemic that made the people recognize the benefits of tourism development on the society more positively than its costs.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations